Biological Psychology / Sixth Edition - Kalat, James W. (Brooks/Cole Publishing Company, 1998)
Introduction: The Goals of Biological Psychology, Human Behavior in the Context of the Animal Kingdom, Nerve Cells and Nerve Impulses, Synapses and Drugs, The Anatomy and Investigation of the Nervous System, The Development and Evolution of the Brain, Vision, The Nonvisual Sensory System, Movement, Rhythms of Wakefulness and Sleep, The Regulation of Internal Body States, Hormones and Sexual Behavior, Emotional Behaviors and Stress, The Biology of Learning and Memory, Lateralization and Language, Recovery from Brain Damage, Mood Disorders and Schizophrenia, Appendices, Brief and Basic Chemistry, Society for Neuroscience Policies on the Use of Animals and Human Subjects in Neuroscience Research.